Tuning the catalytic activity of colloidal noble metal nanocrystals by using differently charged surfactants. Issue 12 (12th March 2018) - Hu, J. H.; Mi, H.; Wang, N.; Zhu, H. Y.; Guo, W. Y.; Zhang, S. R.; Shi, F.; Lei, Z. B.; Liu, Z.-H.; Jiang, R. B.
Abstract : The catalytic activity of metal nanocrystals is tuned by using differently charged surfactants. Abstract : The catalytic activity of metal nanocrystals is mainly tuned through the control of their shapes and sizes. However, the shapes and sizes of many metal nanocrystals are difficult to control and therefore their catalytic activity is hard to tune. Here, we demonstrate another approach, using differently charged surfactants, for tuning the catalytic activity of metal nanocrystals. Au and Pd nanocrystals capped with cationic cetyltrimethylammonium bromide (CTAB) and anionic citrate are chosen to study the effect of surfactant charges on the catalytic activity. The oxidation of o -phenylenediamine to 2, 3-diaminophenazine by H2 O2 is selected as a model reaction. The prepared Au and Pd nanocrystals are initially capped with CTAB, which is changed to citrate through surfactant exchange. Owing to the relatively weak electrostatic interaction of CTAB with the nanocrystals, the surfactant exchange does not induce observable changes in nanocrystal shapes and sizes. In contrast, the catalytic activity is greatly improved by the surfactant exchange. XPS analysis and theoretical calculations indicate that the adsorption of anionic citrate enriches the electrons of the nanocrystal surfaces, while the adsorption of CTAB depletes the electrons of the nanocrystal surfaces. The different catalytic activities of CTAB and citrate-capped nanocrystals arise from the different behaviors of electron transfer between the surfactants and the nanocrystal surface. Since the surfacants that electrostatically bind to the metal nanocrystals are facile to exchange into other surfactants, our findings provide an effective way to tuning the catalytic activity of metal nanocrystals.